Impact of Microfinance on the Social Development of Beneficiaries of Syangja District, Nepal - Dhakal, Chandra Prasad (Tribhuvan University Journal, 2017)
Microfinance is known as economic crisis manager of rural society. It provides the easy loan along with the skill of financial management and other orientation program. Microfinance is the friend of poor who always become ready to support the poor, marginalized and disadvantage communities. The study aims to identify the social impact of microfinance on the beneficiaries of Syangja district. The data collected were from the 385 beneficiaries of microfinance through structured questionnaire. The study has measured the impact of microfinance on education, healthcare, decision making power and women’s empowerment. There was significant impact observed on the social development of beneficiaries. This study had compared the changes between poor and non-poor as the national standard of poverty. There was significant association between poor and non-poor in the most of cases which had indicated significantly different effect of facilities provided by the microfinance.